In situ X-ray imaging of directed energy deposition of metals: The comparisons of delivery performance between spherical and irregular powders. (July 2022) - Wang, Hui; Gould, Benjamin; Haddad, Marwan; Wu, Ziheng; Wolff, Sarah J.
Abstract: Laser-based powder-blown directed energy deposition (DED) is receiving more and more attention in both academia and industry because it is a competitive method for repairing and remanufacturing. State-of-art DED additive manufacturing processes use both spherical and irregular powders both of which have distinct advantages (e.g. the quality of final built components and fabrication cost respectively). Nowadays, most investigations focus on the comparisons of these two types of powders through the analysis of mechanical and microstructural properties. However, the fundamental differences that cause this variance in properties are still unknown. In situ synchrotron X-ray imaging has proven to be a technique capable of revealing the fundamental physics of phenomena in both DED and laser powder bed fusion processes. Therefore, this study will use this technique to provide a fundamental understanding of how different powders behave in DED AM. Delivery performance comparisons between spherical and irregular powders are conducted in this investigation, including the powder delivery velocity and the interaction between delivered particles and the melt pool.